2020
DOI: 10.1007/s00167-020-05871-3
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and ethnic polymorphism result in considerable mismatch between native trochlear geometry and off-the-shelf TKA prostheses

Abstract: Purpose To determine if trochlear morphology in healthy knees depends on sex and ethnicity, and to compare it to of-theshelf TKA prostheses. Methods Three retrospective series of CT angiograms from France (female, 124; male, 135), China (female, 122; male, 137) and South Africa (female, 21; male, 62) were used to digitize osseous landmarks at the level of the femoral epicondyles. Sulcus angle, trochlear rotation, lateral trochlear inclination, trochlear asymmetry ratio, and trochlear depth index were quantiied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
(46 reference statements)
0
11
0
Order By: Relevance
“…This parameter‐tool duality increases the potential to address multiple challenges simultaneously while remaining compatible with different personalisation strategies and other assistive technologies [25]. Furthermore, custom implants offer three features that are rarely attainable when using off‐the‐shelf implants, which are not designed to be implanted in variable positions: Optimisation of bone‐implant fit: the implanted components are designed to follow the contours of the resected bone surfaces, thus avoiding any prosthetic over‐ or under‐coverage, and hence minimizing the risks of soft‐tissue impingements [1, 2, 15]; Decoupling of the patellofemoral compartment from the tibiofemoral compartment: the trochlear groove can be oriented to optimise patellofemoral kinematics independently from the femoral condyles that should be aligned to optimise tibiofemoral kinematics, which eliminates the need for external rotation of the femoral component [14, 19, 22, 24]; Restoration of native condylar curvature: the sphericity or ‘ovoidicity’ of prosthetic condyles can be adjusted to match the unique anatomy of the individual, to maintain equal ligament tensions throughout the range of knee flexion [6, 27]. …”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…This parameter‐tool duality increases the potential to address multiple challenges simultaneously while remaining compatible with different personalisation strategies and other assistive technologies [25]. Furthermore, custom implants offer three features that are rarely attainable when using off‐the‐shelf implants, which are not designed to be implanted in variable positions: Optimisation of bone‐implant fit: the implanted components are designed to follow the contours of the resected bone surfaces, thus avoiding any prosthetic over‐ or under‐coverage, and hence minimizing the risks of soft‐tissue impingements [1, 2, 15]; Decoupling of the patellofemoral compartment from the tibiofemoral compartment: the trochlear groove can be oriented to optimise patellofemoral kinematics independently from the femoral condyles that should be aligned to optimise tibiofemoral kinematics, which eliminates the need for external rotation of the femoral component [14, 19, 22, 24]; Restoration of native condylar curvature: the sphericity or ‘ovoidicity’ of prosthetic condyles can be adjusted to match the unique anatomy of the individual, to maintain equal ligament tensions throughout the range of knee flexion [6, 27]. …”
Section: Figmentioning
confidence: 99%
“…(1) Optimisation of bone-implant it: the implanted components are designed to follow the contours of the resected bone surfaces, thus avoiding any prosthetic or under-coverage, and hence minimizing the risks of soft-tissue impingements [1,2,15]; Decoupling of the patellofemoral compartment from the tibiofemoral compartment: the trochlear groove can be oriented to optimise patellofemoral kinematics independently from the femoral condyles that should be aligned to optimise tibiofemoral kinematics, which eliminates the need for external rotation of the femoral component [14,19,22,24];…”
mentioning
confidence: 99%
“…Recent studies published by Saffarini et al 20 , 21 and Kuo 22 show that even the so-called patellar friendly implants are not able to restore normal morphology of the anterior femur. Using a patellar implant may therefore help to better match the two components.…”
Section: Current Trends and Controversial Topics In Dealing With The mentioning
confidence: 99%
“…Moreover, the prostheses of conventional TKA cannot cover the wide spectrum of ethnic tibiofemoral morphotypes [25]. Mismatch in the angles of the sulcus between the native knees and prostheses has been proved, however, it is not clear to what extent this is true for other patellofemoral ratios [25,26]. In recent studies, it was shown that four of the five measured trochlear morphometric parameters relied significantly on ethnicity, whereas only two of the measured parameters relied on gender [26].…”
Section: Introductionmentioning
confidence: 99%
“…Mismatch in the angles of the sulcus between the native knees and prostheses has been proved, however, it is not clear to what extent this is true for other patellofemoral ratios [25,26]. In recent studies, it was shown that four of the five measured trochlear morphometric parameters relied significantly on ethnicity, whereas only two of the measured parameters relied on gender [26]. Such research, including anatomical analysis, provides standards for the suitable design of femur and tibia components, taking into account gender or patient-specific differences in the Asian population [24,[27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%